2009
DOI: 10.3329/jsr.v1i2.1625
|View full text |Cite
|
Sign up to set email alerts
|

Antiulcer Activity of Morinda Citrifolia Linn Fruit Extract

Abstract: The study was designed to investigate the antiulcer activity of ethyl acetate extract of the fruits of Morinda citrifolia Linn (Rubiaceae) using different models of gastric and duodenal ulceration in rats. Gastric ulcers were induced by oral administration of ethanol, aspirin and by pyloric ligation and duodenal ulcers were induced by oral administration of cysteamine HCl. The extract was administered at a dose of 200 and 400 mg/kg orally 30 min prior to ulcer induction. Ranitidine (50 mg/kg) was used as a ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In majority of the cases with gastric ulcer, the etiology is unknown; however, it is generally assented that an imbalance between acid and pepsin production and mucosal integrity would be the responsible factor acting via endogenous defence mechanisms as reported by Al Rashdi et al, 2012 [ 27 ]. Peptic ulcers are caused by an imbalance between the protective and the aggressive mechanisms of the mucosa, and are the result of the association of several endogenous factors and aggressive exogenous factors that are related to living conditions [ 37 , 38 ]. It has been reported that significant antiulcer effects could be due to strengthening of gastric mucosa with the enhancement of mucosal defence [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…In majority of the cases with gastric ulcer, the etiology is unknown; however, it is generally assented that an imbalance between acid and pepsin production and mucosal integrity would be the responsible factor acting via endogenous defence mechanisms as reported by Al Rashdi et al, 2012 [ 27 ]. Peptic ulcers are caused by an imbalance between the protective and the aggressive mechanisms of the mucosa, and are the result of the association of several endogenous factors and aggressive exogenous factors that are related to living conditions [ 37 , 38 ]. It has been reported that significant antiulcer effects could be due to strengthening of gastric mucosa with the enhancement of mucosal defence [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ethanol is readily penetrates the gastric mucosa due to its ability to solubilize the protective mucous and expose the mucosa to the proteolytic and hydrolytic actions of hydrochloric acid and pepsin [ 5 ] and also cause profound micro-vascular changes with strong vasoconstriction accompanied by arteriolar dilatation responsible for engorgement of mucosal capillaries [ 8 ]. The pathogenesis of mucosal damage in the stomach is associated with reduction of bicarbonates secretion and generation of ROS that seem to play a vital role in the formation of lipid peroxides, accompanied by impairment of anti-oxidative enzyme activity of cells [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact, most of drugs are associated with adverse reactions (e.g. anaphylaxis reactions, gynecomastia, hematopoietic changes, thrombocytopenia, acute interstitial nephritis, nephrotoxicity and hepatotoxicity) requirement for multiple doses per day, large tablet size, and the need to separate the drug from meals and potentially interacting medications [ 5 ]. Due to those factors, there is a need to find new anti-ulcerogenic compound(s) with potentially less or no side effects and medicinal plants have always been the main sources of new drugs candidates for the treatment of gastric ulcer.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that numerous modern medicines are accessible for healing peptic ulcers, the majority of these pharmaceuticals have serious side effects. Herbal remedies are the basis for new potential candidates, and they have been established to be beneficial in combating both gastric and duodenal ulcers [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acidified ethanol could also induce gastric mucosal injury probably through generation of leukotrienes and activation of 5-lipoxygenase pathway. Leukotriene antagonists and 5-lipoxygenase blockers have been shown to prevent ethanol-induced stomach ulcers [ 33 ]. As a result, the cytoprotective effects of Calpurnia aurea leaf extract might be related to blocking the 5-lipoxygenase pathway or leukotriene activity.…”
Section: Discussionmentioning
confidence: 99%